Risk factors for impaired maternal bonding when infants are 3 months old: a longitudinal population based study from Japan - Nakano M; Upadhyaya S; Chudal R; Skokauskas N; Luntamo T; Sourander A; Kaneko H (BMC, 2022)
BackgroundImpaired maternal bonding has been associated with antenatal and postnatal factors, especially postpartum depression. Only a few population-based, longitudinal studies have examined the association between maternal depression and bonding in outside western countries. In addition, little is known about the association between psychosocial factors during pregnancy and impaired maternal bonding. The aim of this study was to investigate risk factors associated with impaired maternal bonding 3 months after delivery using Japanese population-based, longitudinal study from pregnancy period to 3 months after delivery.MethodsThis study was performed at the public health care center in Hekinan city, Aichi prefecture, Japan. Mothers who participated the infant's health check-up 3 months after delivery from July 2013 to Jun 2015 completed the Postpartum Bonding Questionnaire (PBQ) and the Edinburgh Postnatal Depression Scale (EPDS) 1 month after delivery. Information was also provided from home visit at 1 month after delivery, birth registration form, and pregnancy notification form. The study included 1060 mothers with a mean age of 29.90years, who had given birth at a mean of 38.95weeks.ResultsBivariate and multivariate logistic regression analyses were conducted to identify the association between antenatal and postnatal factors and impaired maternal bonding. The main findings were that maternal negative feelings about pregnancy (OR=2.16, 95% CI=1.02-4.56) and postpartum depression at 1 month after delivery (OR=7.85, 95% CI=3.44-17.90) were associated with higher levels of impaired maternal bonding 1 months after delivery. Mothers who had delivered their first child had increased odds of a moderate level of impaired maternal bonding 3 months after delivery (OR=1.85, 95% CI=1.22-2.81).ConclusionsThe findings emphasize the importance of identifying mothers with depression and those with maternal negative feelings towards pregnancy to assess possible impaired maternal bonding.